Gal‐3 regulates the capacity of dendritic cells to promote NKT‐cell‐induced liver injury. Issue 2 (27th November 2014) - Volarevic, Vladislav; Markovic, Bojana Simovic; Bojic, Sanja; Stojanovic, Maja; Nilsson, Ulf; Leffler, Hakon; Besra, Gurdyal S.; Arsenijevic, Nebojsa; Paunovic, Verica; Trajkovic, Vladimir; Lukic, Miodrag L.
<x xml:space="preserve">Abstract</x> Galectin‐3 (Gal‐3), an endogenous lectin, exhibits pro‐ and anti‐inflammatory effects in various disease conditions. In order to explore the role of Gal‐3 in NKT‐cell‐dependent pathology, we induced hepatitis in C57BL/6 WT and Gal‐3‐deficient mice by using specific ligand for NKT cells: α‐galactosylceramide, glycolipid Ag presented by CD1d. The injection of α‐galactosylceramide significantly enhanced expression of Gal‐3 in liver NKT and dendritic cells (DCs). Genetic deletion or selective inhibition of Gal‐3 (induced by Gal‐3‐inhibitor TD139) abrogated the susceptibility to NKT‐cell‐dependent hepatitis. Blood levels of pro‐inflammatory cytokines (TNF‐α, IFN‐γ, IL‐12) and their production by liver DCs and NKT cells were also downregulated. Genetic deletion or selective inhibition of Gal‐3 alleviated influx of inflammatory CD11c+CD11b+ DCs in the liver and favored tolerogenic phenotype and IL‐10 production of liver NKT and DCs. Deletion of Gal‐3 attenuated the capacity of DCs to support liver damage in the passive transfer experiments and to produce pro‐inflammatory cytokines in vitro. Gal‐3‐deficient DCs failed to optimally stimulate production of pro‐inflammatory cytokines in NKT cells, in vitro and in vivo. In conclusion, Gal‐3 regulates the capacity of DCs to support NKT‐cell‐mediated liver injury, playing an important pro‐inflammatory role in acute liver injury.